Terorisme Dan Agama Dalam Perspektif Charles Kimball - Selvia Santi (Indonesia Center for Middle East Studies, 2017)
In this article the author tries to answer the research question, is it true that religion has encouraged terrorist groups to launch their acts of terror? To answer that, the author will use the thought of a comparative religious scholar who once served in the conflict areas of the Middle East, Charles Kimball, which is described in his book